Systematic Literature Review: Strategic Hr- In Improving Organisational Performance - Sudiarti, Nani; Tussoleha Rony, Zahara; Ali, Hapzi (Dinasti International Journal of Management Science, 2024)
Strategic planning is a dynamic process that can help organizations define long-term goals and develop strategies to achieve them. The purpose of this study is to investigate and evaluate the use of related systems in relation to human resource (HR) management in organizations. This study uses a qualitative design with a descriptive approach. The results of the study show that the use of strategic planning in human resources (HR) management has a positive effect on the achievement of organizational goals. From mission definition to performance evaluation, the strategic planning phase has proven to be a solid foundation for effective human resource management. The result is increased employee motivation and commitment, better use of human resources, and organizational adaptation to environmental changes. Additionally, a continuous evaluation process helps identify areas for improvement and improvement, leading to a smooth and efficient work environment. Overall, this study confirms the importance of integrating planning with human resource development planning for organizational sustainability and success.